Ergonomic risk factors for carpal tunnel syndrome symptoms among nurses at hospital in Melaka - Siti Nor Mirsa, Amiruddin (2018)
This study deals with the ergonomic risk factors for Carpal Tunnel Syndrome symptoms among nurses at hospital in Melaka. The objective of this study are to determine related ergonomic risk factors among nurses, to determine the prevalence of Carpal Tunnel Syndrome (CTS) symptoms among nurses in the hospital and to determine the relationship between the individual factors and prevalence of CTS symptoms among nurses. The design of this study is cross – sectional which involving 48 respondent nurses at the Surgery Department. Individual factors were collected by using socio – demographic form. The Ergonomic risk factors among nurses were identified by using Checklist of Ergonomic Risk Factor and the prevalence or CTS symptoms was calculated from Boston Carpal Tunnel Questionnaire (BCTQ) and analysed by using Statistical Package for Social Science (SPSS). Next, the relationship between the individual factors and prevalence of CTS symptoms among nurses was analysed by using Spearman correlation test. As result, the ergonomic risk factors identified were awkward posture, static and sustained work posture, forceful exertion and repetitive motion. Other than that, the highest average result for symptom severity scale and functional status scale were 1.81 and 1.71 respectively. There is significant correlation between race and duration with the prevalence of CTS symptoms among nurses in Surgery Department based on result obtained. In conclusion, preventive control measure such as improving the working environment and providing knowledge of CTS symptoms can help in reducing the prevalence of CTS symptoms among nurses and ensuring the health, safety and well – being of nurses in the Surgery Department.